23 Replies
@Apu
Note for OP
+solved @user
to close the thread when your doubt is solved. Mention the user who helped you solve the doubt. This will be added to their stats.for
11th you can try using the functional eqn formula and relations for polynomials
I tried using functional eqn but i couldn’t get any results
,rotate
,rotate
$$ f(x+y) = f(x) \cdot f(y) + 3f(x-y)$$
$$ 3f(x) \cdot f(-y) + 3\cdot 3f(x+y)=3f(x-y) $$
$$ 8 f(x+y) + 3f(x) \cdot f(-y) = -f(x) \cdot f(y)$$
Keshav
assuming f(x) is odd
$$ 8 f(x+y) = 2f(x) \cdot f(y) $$
assuming f(x) is even
$$ 8 f(x+y) = -4f(x) \cdot f(y) $$
Keshav
well since its getting too heavy
we can just use value putting
how do i do that? Can u show me
hmm
Comrade Rock Astley
so a_i =0
Try the same for 12
Comrade Rock Astley
the main ideas are to substitute x=y=0, x=0, y=0 and x=y
Oh okay
@Real potato
+solved @Comrade Rock Astley
Post locked and archived successfully!
Archived by
<@1088352651567173632> (1088352651567173632)
Time
<t:1716991549:R>
Solved by
<@769492044837552139> (769492044837552139)